Planning and Designing the Improving Addiction Care Team (IMPACT) for Hospitalized Adults with Substance Use Disorder. Issue 5 (1st May 2017) - Englander, Honora; Weimer, Melissa; Solotaroff, Rachel; Nicolaidis, Christina; Chan, Benjamin; Velez, Christine; Noice, Alison; Hartnett, Tim; Blackburn, Ed; Barnes, Pen; Korthuis, P. Todd
Abstract : People with substance use disorders (SUD) have high rates of hospitalization and readmission, long lengths of stay, and skyrocketing healthcare costs. Yet, models for improving care are extremely limited. We performed a needs assessment and then convened academic and community partners, including a hospital, community SUD organizations, and Medicaid accountable care organizations, to design a care model for medically complex hospitalized patients with SUD. Needs assessment showed that 58% to 67% of participants who reported active substance use said they were interested in cutting back or quitting. Many reported interest in medication for addiction treatment (MAT). Participants had high rates of costly readmissions and longer than expected length of stay. Community stakeholders identified long wait times and lack of resources for medically complex patients as key barriers. We developed the Improving Addiction Care Team (IMPACT), which includes an inpatient addiction medicine consultation service, rapid‐access pathways to posthospital SUD treatment, and a medically enhanced residential care model that integrates antibiotic infusion and residential addiction care. We developed a business case and secured funding from Medicaid and hospital payers. IMPACT provides one pathway for hospitals, payers, and communities to collaboratively address the SUD epidemic.